The Initiation of European Annals of Dental Sciences - Tuğba Bezgin (European Annals of Dental Sciences, 2021)
On behalf of the Edito- rial Board, I am delighted to announce the publica- tion of the first issue of the European Annals of Dental Sciences. European Annals of Dental Sciences is the of- ficial scientific publica- tion of Ankara University Faculty of Dentistry. This journal was first introduced in 1972 under the name of "Ankara Üniversitesi Diş Hekimliği Fakültesi Dergisi / Journal of Ankara University Faculty of Dentistry". Since then, it had made significant scientific contributions to the field of dentistry. Now, almost after 50 years, we have renamed our publication European Annals of Dental Sciences in 2021 and changed the publication language to English to facilitate an effective world-wide transmission of new and innovative research and knowledge related to dentistry. Our Editorial Board now includes mentors with robust academic background from different dental specialties who surely will enhance our publication quality. This issue owes much to many people. Thanks are due first to Profes- sor Erhan Ozdiler, the former Editor-in-Chief, for his unfailing support. His commitment to research is inspiring. As incoming editors, we will try to keep his legacy alive. We, on behalf of the Editorial Board, dedicate our first issue to him. I would like to extend a big thank you to our Dean, Professor Kaan Orhan. It is a privilege to work with a leader like him. We are honored by the trust he placed in us and will do our best to increase the quality of the journal to the higher levels it deserves. We are also grateful to our Vice Dean, Associate Professor Mehmet Eray Kolsuz for his support. Most of all, my endless thanks are to my co-editors, Associate Professors Gülbike Demirel and Ismail Hakkı Baltacıoğlu, who have so generously dedicated their time and expertise to make this project happen. No detail, large or small, has been beyond their notice. Their professionalism, good friendship and hard work have made this issue possible. Our special gratitude must also go to the members of our Editorial Board, whose role has been vital in ensuring that the journal maintains a high standard. I also would like to thank the reviewers of this first issue who admirably spend their valuable time to review our articles and all authors who contributed manuscripts. We hope our readers will enjoy reading our first issue, and that EADS will continue to successfully share the good quality dental knowledge with a wider audience.